2021
DOI: 10.3390/polym13071093
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Bond Integrity of Filled and Unfilled Resin Adhesive Enhanced with Silica Nanoparticles—An SEM, EDX, Micro-Raman, FTIR and Micro-Tensile Bond Strength Study

Abstract: The objective of this study was to synthesize and assess unfilled and filled (silica nanoparticles) dentin adhesive polymer. Methods encompassing scanning electron microscopy (SEM)—namely, energy dispersive X-ray spectroscopy (EDX), micro-tensile bond strength (µTBS) test, Fourier transform infrared (FTIR), and micro-Raman spectroscopy—were utilized to investigate Si particles’ shape and incorporation, dentin bond toughness, degree of conversion (DC), and adhesive–dentin interaction. The Si particles were inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
7
20
0
Order By: Relevance
“…According to the ISO standard number 11,405, TC of dental materials within a temperature range of 5 to 55 °C is suitable to offer aging for a limited time [ 36 ]. It has been observed in several previous studies that the bond strength decreases after aging [ 37 , 38 ], and our results have echoed similar findings as a decreased μTBS was also observed for the two groups after aging.…”
Section: Discussionsupporting
confidence: 92%
“…According to the ISO standard number 11,405, TC of dental materials within a temperature range of 5 to 55 °C is suitable to offer aging for a limited time [ 36 ]. It has been observed in several previous studies that the bond strength decreases after aging [ 37 , 38 ], and our results have echoed similar findings as a decreased μTBS was also observed for the two groups after aging.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier, Bin-Shuwaish et al also reported an inverse positive linear relationship between increasing GO content and DC [ 32 ], and our results agree with their findings. Aside from rGO, researchers have also previously incorporated various other inorganic fillers like hydroxyapatite and silica in the adhesive and reported a similar trend (DC decreases linearly with the increasing filler content) [ 27 , 47 ]. A logical reason to explain this could be the nature of the inorganic fillers, which are opaque to the light, possibly hindering the adequate conversion of monomers into polymers, thus, resulting in low DC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…After polymerizing the adhesive resins for 40 s with a curing light, the FTIR peaks were observed again. Using the method of Alhenaki et al [24], C-C aromatic reference peaks (1607 cm −1 ) and C=C (aliphatic) absorbance peaks (1638 cm −1 ) were collected. To determine the DC, FTIR spectra were appreciated between 400 and 4000 cm −1 .…”
Section: Ftir Spectroscopy and DC Analysismentioning
confidence: 99%